After American Exceptionalism: 21st century “Thucydides trap” - Koljević Griffith, Bogdana (Sociološki pregled, 2022)
In the centre of this interdisciplinary investigation is the issue of primary political, philosophical and social foundations of the project of liberal hegemony – as well as real-political end of this discourse in the 21stcentury. The politics of interventionism and human rights is opposed to the politics of sovereignty in such a way that the structural difference between the 20th century Western elitism and the perspective of the multipolar world is the differentiation between hierarchical systems of power and politics of equality. The constitutive part of these processes is “the rebirth of history” through which a more just order is to be established and political consequences for the world will significantly depend on whether crypto-idealistic i.e., “Wilsonian school” will prevail in the USA. Therefore, the issue whether it is possible to avoid “Thucydides Trap” in the 21st century refers to the difference between “necessary America” and “independent America”. Multipolarity as the basis of true multilateralism appears as a potentially new model for the implementation of the politics of sovereign equality.